Screening of Phytochemicals in Clitoria Ternatea Flowers and their Antimicrobial Potential - CHRISTINA ISAAC; VALIVITTAN.K (International Journal of Pharma and Bio Sciences, 2018)
Plants have been used to cure many ailments in traditional systems of medicine. Hence plants and their products can be validated for their therapeutic potential. The flowers of the plant Clitoria ternatea was chosen for present study. The methanolic extract of the flower was subjected to phytochemical study and the presence of major phytochemicals were detected. DPPH activity for free radical scavenging action was done, by UV spectrophotometer at 517nm. Anti-microbial activity was studied against E.Coli. Staphylococcus aureus, Bacillus spp, Salmonella typhi, Pseudomonas aeruginosa, Candida albicans, Aspergillus niger, Rhizopus spp and Trichoderma viride. The flower extract was found to be an effective antimicrobial agent. It also exhibited anti-oxidant property. Thus the flower of Clitoria ternatea was found to be of therapeutic and industrial value.